Human Resource Management in Islamic Educational Institutions at Integrated Islamic Junior High Schools - Dini Febriyenti; Jamilus Jamilus (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
This study aims to describe the Management of Human Resources in Islamic Education Institutions at SMPIT Qurrata A'yun Batusangkar. This research is included in qualitative research due to the method used by researchers through descriptive methods. Data obtained through observation, interviews, personal documentation and other official documentation. The results obtained from this study are that the Management of Human Resources in Islamic Education Institutions continues to be optimized to achieve the goals of Islamic educational institutions. This can be seen from some of the problems encountered including, Concept, Planning and Analysis of HR work, Recruitment of staff at SMPIT Qurrata A'yun Batusangkar, Selection and placement of staff at SMPIT Qurrata A'yun Batusang, employee workforce development SMPIT Qurrata A'yun Batusangkar